(untitled) (Journal of the Association for the Study of Australian Literature, 2014)
Malouf’s juvenilia and early adult writing have not yet received scholarly attention. While briefly considering five of his short stories published between 1948 and 1955, this article argues that themes that stretch across the ’longer breath’ of his works, such as a character’s struggle for survival and quest for happiness, are apparent from the time of his schoolboy writing just after World War II. The kinds of life-accounting that Malouf grew up with may have influenced the narrative forms with which the young writer experimented, a view of juvenilia put forward by Alexander (2005) and Eakin (1999). The influence of cinema and modernist authors becomes apparent as his enters his twenties, together with the personal ’writing school’ he discovered in reading Sean O’Faolain’s ’The Short Story’. A reassessment is needed of the general view that Malouf is a poet first who came later to prose, given the evidence of these carefully crafted stories.